Macrophage-Derived Small Extracellular Vesicles in Multiple Diseases: Biogenesis, Function, and Therapeutic Applications - Ye, Jingyao; Liu, Xuehong (Frontiers in Cell and Developmental Biology, 2022)
Mononuclear macrophages (Mφs),innate immune cells, play a pivotal role against pathogens and many diseases, such as cancer, inflammation, cardiovascular diseases, orthopedic diseases, metabolic disorders and so on In recent years, an increasing number of studies have shown that Exos derived from Mφs (M-Exos) play an important role in these diseases, , suggesting that Mφs carry out their physiological functions through Exos. This paper reviews the mechanisms underlying M-Exos production via different forms of polarization and their biological functions in multisystem diseases. In addition, the prospects of M-Exos in disease diagnosis and treatment are described.